Stromal tumor-infiltrating lymphocytes evaluated on H&E-stained slides are an independent prognostic factor in epithelial ovarian cancer and ovarian serous carcinoma - Hwang, Chungsu (Oncol Lett, 2019)
Studies on tumor-infiltrating lymphocytes (TILs) in epithelial ovarian cancer (EOC) have focused on the clinical significance of inflammatory cells of specific subtypes that are identifiable using immunohistochemistry. However, the subtypes of inflammatory cells that reportedly affect patient survival and prognosis have differed from study to study, and few studies have examined TILs using hematoxylin and eosin (H&E) staining. Therefore, the present study aimed to identify the clinical importance of general stromal TILs in EOC by using H&E staining to apply breast cancer recommendations from the International TILs Working Group 2014 on breast cancer using H&E staining. Stromal TILs in 256 EOC cases from Pusan National University Hospital and 475 cases of high-grade serous carcinoma from The Cancer Genome Atlas dataset were assessed. Stromal TILs were evaluated using H&E-stained slides according to the breast cancer recommendations of the International Working Group 2014, and patients were classified into low and high stromal TIL groups according to their stromal TIL values. The associations of these groups with clinicopathologic factors were assessed, and it was confirmed that group membership correlated with survival and prognosis. According to the χ(2) assessment, the stromal TIL group was associated with tumor grade. Furthermore, the stromal TIL group was associated with overall survival according to Kaplan-Meier analysis with the log-rank test. Finally, the stromal TIL group was an independent prognostic factor according to univariate and multivariate Cox regression analyses. In cases of EOC, the evaluation of general stromal TILs on H&E-stained slides could be used to predict prognosis.